2008
DOI: 10.1074/jbc.m710574200
|View full text |Cite
|
Sign up to set email alerts
|

Sortilin-related Receptor with A-type Repeats (SORLA) Affects the Amyloid Precursor Protein-dependent Stimulation of ERK Signaling and Adult Neurogenesis

Abstract: Sortilin-related receptor with A-type repeats (SORLA) is a sorting receptor that impairs processing of amyloid precursor protein (APP) to soluble (s) APP and to the amyloid ␤-peptide in cultured neurons and is poorly expressed in patients with Alzheimer disease (AD). Here, we evaluated the consequences of Sorla gene defects on brain anatomy and function using mouse models of receptor deficiency. In line with a protective role for SORLA in APP metabolism, lack of the receptor results in increased amyloidogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 38 publications
6
87
1
Order By: Relevance
“…Using SorLA-deficient mice, we have found that in the absence of SorLA, AD pathology is strongly accelerated, suggesting a proximal role of SorLA in AD (18,19) that has led to the current model in which SorLA protects against AD (20).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
See 1 more Smart Citation
“…Using SorLA-deficient mice, we have found that in the absence of SorLA, AD pathology is strongly accelerated, suggesting a proximal role of SorLA in AD (18,19) that has led to the current model in which SorLA protects against AD (20).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Numerous studies have indicated that SorLA activity decreases APP processing in several cell lines (10,11,18,23). Although SorLA plays a direct role as a Golgi-localized retention factor that influences the amount of APP processed in sub- JOURNAL OF BIOLOGICAL CHEMISTRY 3363 sequent cellular compartments (22), it remains unknown whether SorLA overexpression per se affects the processing machinery, i.e.…”
Section: Sorla Minimentioning
confidence: 99%
“…GJA1 directly regulates excitatory amino acid transporter 2 (SLC1A2) expression and function and modulates the activity of intracellular signal molecules, which in turn leads to its downregulation (Morioka et al, 2015 Mitogen-activated protein kinase kinase 1 (MAP2K1) has an important role in neuron differentiation and projection (Mace et al, 2013). The activity of MAPK signaling is markedly increased in AD brains (Rohe et al, 2008). The carbohydrate metabolism-related proteins showed increased protein level in CCH rats.…”
Section: Relationships Of Chronic Cerebral Hypoperfusion Altered Synamentioning
confidence: 99%
“…We and others have shown that sorLA binds APP and retains it in the Golgi compartment, thereby preventing processing of the precursor into A␤ (Andersen et al, 2005(Andersen et al, , 2006Offe et al, 2006;Schmidt et al, 2007;Dodson et al, 2008;Rohe et al, 2008). Accordingly, single nucleotide polymorphisms in SORL1, the gene encoding sorLA, are associated with late-onset AD, and sorLA expression is reduced in vulnerable brain regions of AD patients (Scherzer et al, 2004;Andersen et al, 2005;Dodson et al, 2006;Rogaeva et al, 2007).…”
Section: Introductionmentioning
confidence: 99%